The Influence Organizational Culture, Motivation, and Work Discipline Employee Performance - Cyntia, Ade Ilham; Widodo, Zandra Dwanita; Darsono, Darsono (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the influence of organizational culture, work motivation, and work discipline on employee performance at CV Roja Tulus Persada. The research method used is quantitative with data collection through questionnaires distributed to 62 employees. The data analysis technique uses multiple linear regression with the help of the SPSS version 25 application. The results of the study indicate that organizational culture, work motivation, and work discipline partially have a significant effect on employee performance. The organizational culture variable has a t- value of 3.251 (Sig. 0.002), work motivation of 3.851 (Sig. 0.000), and work discipline of 4.496 (Sig. 0.000). Simultaneously, this third variable also has a significant effect on employee performance with a calculated F value of 22.215 (Sig. 0.000). The coefficient of determination (Adjusted R²) value of 0.505 indicates that 51% of employee performance variability can be explained by organizational culture, work motivation, and work discipline. This finding indicates the importance of managing a positive organizational culture, providing effective work motivation, and implementing consistent work discipline in improving employee performance at CV Roja Tulus Persada.